Experimento de fluxo de sedimentos em um segmento de campo de dunas eólicas costeiras de Jenipabu - Litoral oriental do Rio Grande do Norte. - Malta, Júlia Varella (2012)
This study analyzed measurements of the aeolian transport using vertical sand traps across the field dunes of Jenipabu, in the municipality of Extremoz, Rio Grande do Norte state to the North of Natal city. These measurements were used as parameters for the sand aeolian transport in the region. Before the field trips a map of landscape units was made. Three visits to the field were done in September 2011 (field a - the 13th, field b - the 21st, field c - the 29th), period of the year with the highest wind speed, and another in December 8th, 2011 (field d ) when the wind speed starts to decrease. The sand traps used were of the type "I" with collecting opening of 25 cm from the surface level, and type "S" with collecting opening of 25 cm located 25 cm from the surface level in six collecting points in two of the visits (fields a and d ), and sand traps of the type "T" with the collecting opening of 50 cm from the surface level in the other field trips (fields "b" and "c"). A set of records was also collected by using a portable meteorological station complemented with information such as frequency and intensity of winds, precipitation and relative air humidity in the region, from the Estação Meteorológica de Natal , located 12 km from the study area. The sediments collected were treated and the data obtained permitted calculating the ratio of sediment transport. In September, the sedimentation ratio varied from 0.01 to 11.39 kg.m-1.h-1 and in December this ratio varied from 0.33 to 1.30 kg.m-1.h-1 in the type T collectors. In type I collectors they ranged from 0.01 to 11.39 kg.m-1.h-1, while the same parameters varied from 0.01 to 0.73 kg.m-1.h-1 in type S collector. Based on the statistical analysis done, we concluded that the sediment transport increased proportionally to the wind speed 25 cm from the surface. However, this is not true above 25 cm from the surface. The transport of sediments is more intense near the surface where sedimentation ratios greater than 10 kg.m-1.h-1 were found, whilst a maximum value of 3 kg.m-1.h-1 was observed 25 cm below the surface. The volume of sediments collected increases with the increasing wind speed at the surface level, whereas this relationship is opposed far away from that surface